2012
DOI: 10.1002/jbmr.1774
|View full text |Cite
|
Sign up to set email alerts
|

A prospective study of thyroid function, bone loss, and fractures in older men: The MrOS study

Abstract: Excess thyroid hormone is associated with increased bone loss and fracture risk in older women, but few data exist in men. We sought to determine if thyroid function is independently associated with bone loss and fracture risk in older men. Data were analyzed from the Osteoporotic Fractures in Men (MrOS) Study, a cohort of community-dwelling US men aged 65 years and older. Using a case-cohort design, fasting baseline serum archived at −80C was assayed for thyrotropin (TSH) and free thyroxine (FT4) in 397 men w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
61
2

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 60 publications
(71 citation statements)
references
References 42 publications
5
61
2
Order By: Relevance
“…Albeit often used in epidemiologic studies, self-reporting is less reliable than laboratory measurements (37). Most studies report hyperthyroidism to be a risk factor for fractures (6,7,8,9,11,12), and even subclinical hyperthyroidism has been associated with increased fracture risk (13,14). Moreover, studies have reported increased fracture risk related to hypothyroidism (6,10,12) as well as to differences in thyroid function within the reference range (13,17,18).…”
Section: Discussionmentioning
confidence: 99%
See 4 more Smart Citations
“…Albeit often used in epidemiologic studies, self-reporting is less reliable than laboratory measurements (37). Most studies report hyperthyroidism to be a risk factor for fractures (6,7,8,9,11,12), and even subclinical hyperthyroidism has been associated with increased fracture risk (13,14). Moreover, studies have reported increased fracture risk related to hypothyroidism (6,10,12) as well as to differences in thyroid function within the reference range (13,17,18).…”
Section: Discussionmentioning
confidence: 99%
“…Most studies report hyperthyroidism to be a risk factor for fractures (6,7,8,9,11,12), and even subclinical hyperthyroidism has been associated with increased fracture risk (13,14). Moreover, studies have reported increased fracture risk related to hypothyroidism (6,10,12) as well as to differences in thyroid function within the reference range (13,17,18). However, especially outside the hyperthyroid range, no relation between levels of thyroid function and fracture risk has also frequently been reported (7,13,14,20), and there is even one study where self-reported previous hyperthyroidism appeared to decrease foot fracture risk (19).…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations